Study on the Physico-Chemical Properties of the Si Nanowires Surface - Rosaria A. Puglisi; Corrado Bongiorno; Giovanni Borgh; Enza Fazio; Cristina Garozzo; Giovanni Mannino; Fortunato Neri; Giovanna Pellegrino; Silvia Scalese; Antonino La Magna (Nanomaterials, 2019)
Silicon nanowires (Si-NWs) have been extensively studied for their numerous applications in nano-electronics. The most common method for their synthesis is the vapor−liquid−solid growth, using gold as catalyst. After the growth, the metal remains on the Si-NW tip, representing an important issue, because Au creates deep traps in the Si band gap that deteriorate the device performance. The methods proposed so far to remove Au offer low efficiency, strongly oxidize the Si-NW sidewalls, or produce structural damage. A physical and chemical characterization of the as-grown Si-NWs is presented. A thin shell covering the Au tip and acting as a barrier is found. The chemical composition of this layer is investigated through high resolution transmission electron microscopy (TEM) coupled with chemical analysis; its formation mechanism is discussed in terms of atomic interdiffusion phenomena, driven by the heating/cooling processes taking place inside the eutectic-Si-NW system. Based on the knowledge acquired, a new efficient etching procedure is developed. The characterization after the chemical etching is also performed to monitor the removal process and the Si-NWs morphological characteristics, demonstrating the efficiency of the proposed method and the absence of modifications in the nanostructure.